Pelatihan Pengolahan Data Berbasis Komputer Bagi Peneliti Pemula - Nina Zakiah; Muhammad Irwanto; Santi Nurul Fianti (LPPM UMRI, 2020)
Based on the observations we conducted on the students, it can be concluded that most students faced difficulties in processing research data to complete the thesis. This was due to the lack of students' understanding of research methodology and statistics as well as the students’ minimum ability to use the help of a data processing application in a computer, such as SPSS. Based on this problem, we took an initiative to carry out a community service program specifically for students who were conducting research with the theme